Source Apportionment of Air Particulate Matter in Ulaanbaatar City (2017–2019) Using Positive Matrix Factorization - Алтанхуяг, Маралмаа (Scientific transaction of the National University of Mongolia. Physics, 2025)
In the study, the source apportionment of ambient particulate matter was conducted using Positive Matrix Factorization (PMF) based on measurement data from 176 samples of PM₂.₅ and PM₁₀–₂.₅ collected during the winter seasons of 2017–2019 in Ulaanbaatar city. The input dataset included concentrations of 17 chemical elements and black carbon. The PMF results revealed five major sources for both PM₂.₅ and PM₁₀–₂.₅: soil dust (34.8% and 59.2%), coal combustion (39.8%, 18.1%), vehicular emissions (8.1%, 8.5%), petroleum-related sources (4.4%, 2.7%), and industrial emissions (12.9%, 11.6%), respectively.